Impact of COVID 19 on Steel Industry – A case Study of RINL, Visakhapatnam Steel Plant - Pradosh Kumar Rath; Prof. B. Mohan Venkata Ram (International Journal of Engineering and Management Research, 2021)
Steel is by far, the most widely used and is environment friendly as it can be recycled 100%. Steel has wide variety of applications in day to day life. Indeed, steel is the backbone and support of the global economy and infrastructure. Steel has got many forward linkages with manufacturing industries. Status of global steel industry before the onset of COVID 19 and the effect of pandemic on industry in both global and Indian contexts were discussed. The status of Indian economy was briefly explained and projected outlook for steel market after breakout of the pandemic. The effect of COVID on RINL was discussed in detail and various strategies adopted by the industry during the period were explained. Handling of such future eventualities were addressed. After the outbreak, the recovery and outlook were explained in detail. Interventions and initiatives sought from the Government were presented in this paper.